Thermal therapy in health: Categorization of therapeutic indications for natural mineral waters in the region of Beira interior of Portugal - Araújo, André (2016)
Portugal is one of Europe's richest countries in thermal waters [1], and the majority of Portuguese thermal resorts are distributed by northern and central regions. The thermalism comprises the use of natural mineral water and other complementary means for prevention, treatment, rehabilitation or wellness [2]. The use of such water, also known as mineral-medicinal water, for therapeutic purposes has always been aroused a continuous interest in carrying out the characterization of this type of waters and the establishment of an eventual relationship for the treatment of a specific pathological condition. Thermal waters can be defined by waters from the subsoil, which are generated in specific geologic conditions and presenting "physico-chemical dynamism" [3,4]. Thermal mineral water has three fundamental characteristics: it originates naturally from the earth, it is bacteriologically pure and has therapeutic potential [3,4]. Most thermal waters are originated from the water resulting from precipitation, and with its infiltration in depth, they acquire particular physico-chemical characteristics, depending on the mineralogical composition of the geological formations through the water flows [1]. In fact, the geological variability in Portugal enables the occurrence of thermal waters with a high diversity in terms of physico-chemical composition [4]. Thermal waters are classified according to parameters such as temperature, osmotic pressure, radioactivity, chemical composition and mineralisation, being the latter two considered of greater importance [5]. The various therapeutic effects described with thermal therapy have been attributed to its physico-chemical composition, being classified as bicarbonated, sulfated, chlorided, sulphurous, hiposaline and gasocarbonic waters, and this correlation has been the basis for the indication of the different thermal resorts for different disorders of several vital systems of the body, and it is precisely in this context that the existing data are more controversial. From a simplistic and reductionist point of view, most Portuguese thermal waters are described as weakly mineralized, sulphurous, bicarbonated or chlorinated and sodium type waters. In the present work, a literature review was undertaken in order to create an index of information of physico-chemical composition of thermal waters of the Beira Interior region and its therapeutic indications, followed by an exhaustive statistical analysis to assess the correlation between the different physico-chemical parameters and the therapeutic indications described for that thermal waters. The results obtained allow us to demonstrate the role of the major components of the thermal waters to a particular therapeutic effect and hence to create a useful tool for regional typology of the thermal waters in Portugal as a valuable alternative of the therapeutic armamentarium for well and specific-oriented pathological disturbs.